Body Language Used by The Main Characters in Joel Crawford’s Movie “The Croods: A New Age” - Futri, Futri; Sahril, Sahril; Iskandar, Iskandar (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
Based on this descriptive research, the research formulates two research questions as follow: What are the types of body language used by the main characters in Joel Crawford’s movie “The Croods: A New Age?” What are the functions of body language used by the main characters in Joel Crawford’s movie “The Croods: A New Age? The researcher provides an overview related to the data collection and data analysis uses qualitatif research. The researcher found 4 types of body language in accordance with the theory expressed by Mehrabian (2017). The second research question, researcher found the function contained of body language in the movie The Croods A New Age. Based on the theory expressed by Mulyana (2010), for body language, 33 extracts were found. Where for the body language of facial expression type there are 14 data, for the body language of gestures type there are 16 data, then for the body language of gestures type there are 2 data found, then for the body language of voice intonation type there are 2 data.For function, there are five functions of body language, namely repetition, accentuation, complement, contradiction, substitution and regulation.Keywords: Communication, non-verbal, Joel Crawford, movie